DIVERSITY AND GREEN TYPES CARRYING CAPACITY BALI BEEF IN OIL PALM PLANTATION IN KOLAKA DISTRICT - Pagala, Muhammad Amrullah; Munadi, La Ode; Zulkarnain, Deki (Pascasarjana Universitas Sulawesi Tenggara, 2019)
This study aims to observe the diversity of species and forage dominance while analyzing the carrying capacity based on the area of forage produced in the area of oil palm plantations. The research sample was carried out by way of tapping which was carried out at 3 different locations namely Watubangga District, Tanggetada District and Polinggona District which were the basis for the development of oil palm plantations. The results showed that there were 24 forage species divided into 9 families, namely Graminae, Cyperaceae, Polypodiceae, Rubiaceae, Verbenaceae, Aspleniaceae, Asteraceae, Mimosaceae, and Leguminaceae. As for types of forage that can be used as animal feed for 3 families, namely Graminae, Cyperaceae, and Leguminacea. The results of the carrying capacity analysis show that oil palm plantations can only accommodate as many as 59.30 cattle of Bali cattle (ST).Keywords: Forage Type, Carrying Capacity, Palm Oil, Bali Cattle